T.S. Eliot and the tradition of Christian mysticism: the spatial paradox in Burnt Norton - Schmelzer, Felix (TEOLITERARIA - Revista de Literaturas e Teologias, 2017)
The present article seeks to identify T.S. Eliot’s affinity to the tradition of Christian mysticism by analyzing the spatial paradox in the poem Burnt Norton, the first of the Four Quartets. Parting from a general reflection on the importance of the paradox with regard to God’s ineffability, the poem is analyzed from a spatial perspective. It becomes obvious that the spatial paradox is not only used as an argumentative pattern, but also as a compositional key element that structures the whole text, generating a particular down-up-down dynamic. The most curios aspect, in this context, is that the poem continuously formulates and subsequently denies its own spatial movement, thus, in the end, also denying itself.